2019
DOI: 10.1373/clinchem.2018.296681
|View full text |Cite
|
Sign up to set email alerts
|

Independent Validation of a Diagnostic Noninvasive 3-MicroRNA Ratio Model (uCaP) for Prostate Cancer in Cell-Free Urine

Abstract: BACKGROUND Detection of prostate cancer (PC) based on serum prostate-specific antigen (PSA) testing leads to many unnecessary prostate biopsies, overdiagnosis, and overtreatment of clinically insignificant tumors. Thus, novel and more accurate molecular biomarkers are required. METHODS Using reverse transcription quantitative PCR, we measured the concentrations of 45 preselected microRNAs (miRNAs) in extracellular vesicle-enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Moreover, selected miRNAs regulate various signaling pathways that guarantee higher sensitivity and stability of the diagnostic panel. Previously, some researchers also attempted to create a diagnostic panel for the differential diagnosis of PCa and BPH patients based on the analysis of three (miR222-3p * miR-24-3p/miR-30c-5p) siRNAs (after checking 45 siRNA candidates) in clarified urine [49] and two siRNAs (miR 100/200b) in cell urine sediment [50]. The authors showed that such tests can be useful as an adjunct to PSA [in patients with PSA levels in the "gray area" (4-10 ng/mL)] to confirm the need for a prostate biopsy, but they cannot be used as stand-alone tests for diagnosing PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, selected miRNAs regulate various signaling pathways that guarantee higher sensitivity and stability of the diagnostic panel. Previously, some researchers also attempted to create a diagnostic panel for the differential diagnosis of PCa and BPH patients based on the analysis of three (miR222-3p * miR-24-3p/miR-30c-5p) siRNAs (after checking 45 siRNA candidates) in clarified urine [49] and two siRNAs (miR 100/200b) in cell urine sediment [50]. The authors showed that such tests can be useful as an adjunct to PSA [in patients with PSA levels in the "gray area" (4-10 ng/mL)] to confirm the need for a prostate biopsy, but they cannot be used as stand-alone tests for diagnosing PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al (50) revealed that miR-222-3p was negatively associated with clinical staging and lymph node metastasis status in plasma samples collected from patients with oral carcinoma, and miR-222-3p may be a useful diagnostic biomarker for the differentiation of oral squamous cell carcinoma and oral leukoplakia plaque. Furthermore, Fredsoe et al (51) developed a three-microRNA ratio model (miR-222-3p*/miR-24-3p/miR-30c-5p), which provided accurate markers in the differential diagnosis of benign prostatic hyperplasia and prostate cancer (PCa). Several studies have found that serum miRNAs could be used to predict the risk of non-muscle invasive bladder cancer, and risk scores were generated according to the combination of the three miRNA ratios (miR-29a-3p/miR-222-3-p, miR-150-5-p/miR-331-3p and miR-409-3-p/miR-433-5-p) (52,53).…”
Section: Clinical Value Of Mir-222-3p In Cancer Tissuesmentioning
confidence: 99%
“…We measured the expression levels of 92 miRNAs in plasma from all patient groups using a miRNA reverse transcriptase-polymerase chain reaction platform from Exiqon (Vedbaek, Denmark). Briefly, total RNA was extracted from 200 µL serum using the miRCURY™ RNA isolation kit, biofluids (Exiqon, Vedbaek, Denmark) according to the manufacturer's description and stored at −80 • C. Next, 10 µL RNA was reverse transcribed using the miRCURY LNA™ Universal RT microRNA PCR, Polyadenylation, and cDNA synthesis kit (Exiqon) followed by expression analysis by PCR using universal RT Pick-&-Mix microRNA PCR panels, V4.R (Exiqon, Vedbaek, Denmark), according to the manufacturer's description and as described in detail previously [14,21].…”
Section: Cohort Characteristicmentioning
confidence: 99%
“…miRNAs are short non-coding RNAs approximately 22 nucleotides in length, which post-transcriptionally regulate gene expression of up to 60% of all human mRNAs and often play a significant role in oncogenesis [13,17,18]. Dysregulation of miRNA expression in PC has previously been demonstrated in both tumor tissue samples and liquid biopsies [19][20][21][22][23][24]. Coupled with the high stability of miRNAs in biofluids [25], this makes them particularly appealing targets as minimally invasive biomarkers.…”
Section: Introductionmentioning
confidence: 99%